Enantioselective total synthesis of altersolanol A and N. Issue 13 (1st July 2019) - Mechsner, Bastian; Böse, Dietrich; Hogenkamp, Fabian; Ledermann, Nadia; Hartmann, Rudolf; Bochinsky, Kevin; Frey, Wolfgang; Pietruszka, Jörg
Graphical abstract: Abstract: The development of the first enantioselective total synthesis of altersolanol N is reported. The decisive step of the synthesis is the enantioselective formation of the tetrahydroanthraquinone nucleus by a [4 + 2]-cycloaddition in high yield and with excellent diastereo- and enantioselectivity (>95:5 dr and 95:5 er). In addition, a demanding selective monoacetylation of the OH group at the C-2 position was achieved: an epoxide ring opening with the participation of a neighbouring acetyl group could be established. The route proved to be an efficient alternative to also access enantiomerically pure altersolanol A.